From Antropology to negativity. Philosophy, psychoanalysis and psichology in Foucault’s earliest works - ABEIJON , Matías (Utopía y Praxis Latinoamericana, 2023)
The objective of the research presented is to analyze theoretically the intersections between psychology, psychoanalysis and philosophy in Michel Foucault’s early production throughout the period of 1954 to 1957. It aims to perform a theoretical analysis of the arguments that support a series of evaluative postulates and critiques of psychology and psychoanalysis. In turn, these arguments have an origin in the epistemic analysis of the conditions of possibility that allowed the historic emergence of psychological discourses and practices in the 19th and 20th centuries. Some of the topics to be tackled are the materialistic postulates on mental illness; the reworking of early 20th century philosophical critiques of naturalistic psychology; as well as the inquiry into the conditions resulting in the historic emergence of psychology and psychoanalysis, with the starting point of a philosophy of negativity.